PERBANDINGAN LUAS TUTUPAN SPOON TIPED SETAE MAKSILIPED KEDUA PADA Uca spp. (BRACHYURA: OCYPODIDAE) - Murniati, Dewi Citra (ZOO INDONESIA, 2009)
Murniati, D.C. 2009. Comparative spoon tiped setae coverage of the secondmaxilliped of Uca spp. (Brachyrura: Ocypodidae). Zoo Indonesia 18(1): 1-7. Uca iswell known as a group of small, intertidal Ocypodid crab and it is characterized bysexual dimorphism and males have asymmetry chelipeds. Uca spp. has spoon tipedsetae for feeding. The aim of this study was to compare the spoon tiped setae coverageof the second maxilliped of Uca spp. Uca annulipes, U. coarctata and U. triangulariswere used in this study. The second maxilliped of each crab was removed andobserved under a stereo and a compound microscopes. Nonparametric two-factoranalysis of variance revealed that there were significant differences in spoon tipedsetae coverage among U. annulipes, U. coarctata and U. triangularis. However, therewas no difference in spoon tiped setae coverage among female, male and juvenile.This observation shows that this character is not affected by sex and age.